Konflik Peran, Kepribadian LOC Internal, Kinerja Auditor dan Moderasi Tekanan Anggaran Waktu (Suatu Studi pada Auditor yang Bekerja pada KAP di Surabaya) - Yoosita Aulia; Alberta Esti Handayani (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2019)
This study aims to explain some of the factors that influence auditor performance and TAW moderation on the influence of role conflict and internal LOC personality on auditor performance on auditors working at KAP in Surabaya, especially to prove role conflict and internal locus of control personality influence auditor performance. and prove that TAW is able to strengthen the negative influence of role conflict on auditor performance, and prove that TAW weakens the positive influence of internal locus of control personality on auditor performance. This study uses quantitative methods and PLS-SEM analysis techniques. This study successfully proved that role conflict has a negative effect on auditor performance, internal LOC personality has a positive effect on auditor performance, TAW is able to moderate the influence of role conflict on auditor performance, and TAW cannot moderate the internal LOC personality towards auditor performance